2021
DOI: 10.3389/fphys.2021.694809
|View full text |Cite
|
Sign up to set email alerts
|

Application of Metabolomics to Identify Hepatic Biomarkers of Foie Gras Qualities in Duck

Abstract: Foie gras is a traditional dish in France that contains 50 to 60% of lipids. The high-fat content of the liver improves the organoleptic qualities of foie gras and reduces its technological yield at cooking (TY). As the valorization of the liver as foie gras products is strongly influenced by the TY, classifying the foie gras in their potential technological quality before cooking them is the main challenge for producers. Therefore, the current study aimed to identify hepatic biomarkers of foie gras qualities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In humans, Kalhan et al (2011) showed that plasmatic lactate levels were higher when hepatic steatosis developed [45]. Metabolomic studies performed on duck PLOS ONE livers fed for increasing lengths of time (between 6 and 12 days) showed a positive correlation between liver weight and lactate in plasma (r = 0.62) and in liver (r = 0.98) [16,32]. According to Murphy et al (2001), hyperlactatemia could be the result of cellular hypoxia or hypoperfusion with resulting anaerobic metabolism [46].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In humans, Kalhan et al (2011) showed that plasmatic lactate levels were higher when hepatic steatosis developed [45]. Metabolomic studies performed on duck PLOS ONE livers fed for increasing lengths of time (between 6 and 12 days) showed a positive correlation between liver weight and lactate in plasma (r = 0.62) and in liver (r = 0.98) [16,32]. According to Murphy et al (2001), hyperlactatemia could be the result of cellular hypoxia or hypoperfusion with resulting anaerobic metabolism [46].…”
Section: Plos Onementioning
confidence: 99%
“…Recent studies on the proteins fraction have been carried out on two classes of liver weights, light (weights between 550 and 600 g) and heavy (weights over 700 g) and showed marked differences in energy metabolism, oxidative stress, lipids and proteins metabolisms and in the extracellular membrane reorganization [ 12 ]. Recent metabolomics studies performed on duck livers overfed at 12 weeks of age for different durations (6 or 12 days) have shown that when the duration of overfeeding increases, the average liver weight increases and the hepatic metabolism is oriented towards a reduction of carbohydrate and amino acid metabolism, and the plasma membrane could be damaged [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, geese are used extensively worldwide in the production of luxurious food based on their fatty liver products, e.g., foie gras. The foie gras is generally delicious and delicate in texture, favored by a large number of consumers worldwide, with an extremely large and increasing demand in the international market ( Mozduri et al, 2021 ). In particular, as a world-renowned breed dedicated to fatty livers, the Landes geese are very popular and highly adaptable to their environment ( Hermier et al, 1999 ; Mourot et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%